2003
DOI: 10.1152/ajpgi.00432.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase is involved in acid-induced gastric hyperemia in rats and mice

Abstract: . Inducible nitric oxide synthase is involved in acid-induced gastric hyperemia in rats and mice. Am J Physiol Gastrointest Liver Physiol 285: G154-G162, 2003. First published March 19, 2003 10.1152/ajpgi.00432.2002The role of different isoforms of nitric oxide synthase (NOS) in the gastric mucosal hyperemia, induced by 155 mM luminal hydrochloric acid (pH Ϸ 0.8) without a barrier breaker, was investigated. Rats were anesthetized with Inactin (120 mg/kg ip), and mice were anesthetized with Forene (2.2% in 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…Thus the involvement of iNOS in mucus secretion was studied, and a thinner mucus layer with a lower rate of accumulation in iNOS-deficient mice was determined. This observation supported the gastroprotective role of epithelial iNOS that has been previously suggested (29). These results also explained why the mucus was not affected by L-NNA pretreatment (in a concentration efficient in increasing blood pressure, Refs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus the involvement of iNOS in mucus secretion was studied, and a thinner mucus layer with a lower rate of accumulation in iNOS-deficient mice was determined. This observation supported the gastroprotective role of epithelial iNOS that has been previously suggested (29). These results also explained why the mucus was not affected by L-NNA pretreatment (in a concentration efficient in increasing blood pressure, Refs.…”
Section: Discussionsupporting
confidence: 89%
“…Constitutively expressed iNOS is present in the surface epithelial cells in the mouse corpus (29). Thus the involvement of iNOS in mucus secretion was studied, and a thinner mucus layer with a lower rate of accumulation in iNOS-deficient mice was determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we (29) showed that the hyperemia induced by luminal acid was absent or substantially reduced in iNOS knockout mice. Our results also suggested that iNOS was constitutively expressed in surface epithelial cells.…”
Section: Discussionmentioning
confidence: 88%
“…Blood flow is also important in removing backdiffusing hydrogen ions, toxic waste products, accumulated oxygen metabolites, and other inflammatory mediators (17). We have shown in previous studies (29,35) that luminal acid alone induces hyperemia without any macroscopic lesions. Furthermore, we have suggested that epithelial inducible nitric oxide (NO) synthase (iNOS) is involved in the hyperemic response to acid, possibly signaling to afferent nerves, leading to a blood flow increase.…”
mentioning
confidence: 79%